Treatment of stand-alone atrial fibrillation with a right thoracoscopic approach employing a microwave or monopolar radiofrequency energy source: long-term results - Straka, Zbyněk; Budera, Petr; Osmančík, Pavel; Malý, Marek; Vaněk, Tomáš (Interactive cardiovascular and thoracic surgery, 2016)
OBJECTIVES: Minimally invasive surgery for atrial fibrillation (AF) has rapidly evolved recently. The long-term efficacy of most of these procedures is poorly known. METHODS: Between 2006 and 2010, 38 drug-resistant, symptomatic patients with stand-alone AF underwent unilateral, thoracoscopic, off-pump ablation. The mean age was 60 ± 8.2 (range 42-75) years and the mean AF duration was 46 ± 62 (range 3-240) months. Sixteen patients (42%) had paroxysmal, 9 (24%) had persistent and 13 (34%) had long-standing persistent AF. A box lesion was created using a microwave (26 patients) or monopolar radiofrequency (12 patients) system. Patients were prospectively followed with repeat electrocardiograms (ECGs) and ECG Holters. Additional catheter ablation was offered to patients with recurrence of arrhythmia. RESULTS: All procedures were completed as planned with one conversion to sternotomy, zero mortality and minimal in-hospital complications. The mean follow-up duration was 70 ± 19 (range 20-88) months. Arrhythmia-free survival rates after the procedure were 50, 44.4, 24.1 and 10.8% at 6, 12, 36 and 60 months, respectively, with most recurrences in the first 6 months. Twelve patients underwent additional catheter ablation(s); from the last intervention, 75% of them were in sinus rhythm (SR) with a mean follow-up of 31 ± 23 (range 4-86) months. Overall, at the end of follow-up, only 3 patients were still in SR without any arrhythmia recurrence. Major complications (cerebral, peripheral embolism or bleeding) occurred in 5 patients. CONCLUSIONS: Unilateral, thoracoscopic AF ablation is safe and technically feasible. However, the results of the microwave and monopolar radiofrequency devices were less than satisfactory, with a gradual decline in arrhythmia-free survival over a very long-term follow-up.
Keywords: senioři; torakoskopie; Long-term follow-up; elektrokardiografie; mikrovlny; Time Factors; Česká republika; výsledek terapie; katetrizační ablace; Middle Aged; mužské pohlaví; míra přežití; Adult; Prospective Studies; recidiva; Czech Republic; Cardiac surgery; Follow-Up Studies; Thoracoscopy; Atrial fibrillation; následné studie; Catheter Ablation; Electrocardiography; ženské pohlaví; Humans; prospektivní studie; Recurrence; Microwaves; Survival Rate; fibrilace síní; časové faktory; lidé středního věku; Minimally invasive; dospělí; Female; Aged; Atrial Fibrillation; Thoracoscopic; Treatment Outcome; lidé; Male